A battery
Patent Information
- Application Number
- CN202522545187.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-30
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2035-11-30
AI Technical Summary
[0003]在相关技术中,极耳胶的端部与铝塑膜之间容易形成褶皱,从而影响铝塑膜的密封性能
Smart Images

Figure CN224908194U_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of lithium-ion battery technology, and more particularly to a battery. Background Technology
[0002] Pouch lithium-ion batteries are widely used in portable electronic devices due to their light weight and high energy density, meeting the demands of these devices for lightweight, high-capacity batteries. A typical structure for pouch lithium-ion batteries uses an aluminum-plastic film to encase the cell assembly, exposing the tabs. In this structure, the sealing performance between the aluminum-plastic film and the cell assembly significantly impacts the overall performance of the pouch lithium-ion battery.
[0003] In related technologies, wrinkles easily form between the end of the tab adhesive and the aluminum-plastic film, thus affecting the sealing performance of the aluminum-plastic film. Utility Model Content
[0004] This application provides a battery that can reduce or eliminate wrinkles and improve the battery's sealing performance.
[0005] The first aspect of this application provides a battery, comprising:
[0006] Metal encapsulation film;
[0007] A battery cell assembly is housed within a metal encapsulation film. The battery cell assembly includes a tab assembly extending from one side of the metal encapsulation film. The tab assembly includes a tab and tab adhesive covering the tab. Along the width direction of the tab adhesive, the tab adhesive includes a main body segment, an edge segment disposed at at least one end of the main body segment along its width direction, and a pressing segment connecting the main body segment and the edge segment. The thickness of the pressing segment at the end closer to the main body segment is greater than the thickness of the pressing segment at the end farther from the main body segment. The edge segment includes a reduced-thickness segment and a non-reduced-thickness segment. Along the thickness direction of the tab adhesive, the thickness of the reduced-thickness segment is smaller than the thickness of the non-reduced-thickness segment.
[0008] The tab adhesive and the metal encapsulation film are thermally fused together to form a thermally fused zone. Along the length of the tab adhesive, the thermally fused zone includes a first thermally fused zone corresponding to the thickened section and a second thermally fused zone corresponding to the non-thickened section. The length of the first thermally fused zone is less than the length of the second thermally fused zone.
[0009] According to the battery described in the first aspect of this application, the thickened section in the edge segment facilitates the formation of a thermally fused connection between the tab adhesive and the metal encapsulation film. During the connection process between the metal encapsulation film and the thickened section, the two will not bend significantly, thereby reducing or eliminating wrinkles and improving the battery's sealing performance. On the other hand, the thermally fused area in the embodiments of this application includes a first thermally fused area corresponding to the thickened section and a second thermally fused area corresponding to the non-thickened section. By setting the length of the second thermally fused area to be greater than the length of the first thermally fused area, the battery's lifespan can be effectively balanced while ensuring the overall encapsulation performance, thus preventing leakage.
[0010] In one possible implementation, the length of the second hot-melt zone is L2, and the length of the first hot-melt zone is L1, wherein L1 and L2 satisfy the following relationship:
[0011] L2-L1≥5μm.
[0012] In one possible implementation, the battery has a capping region formed on one side edge of the metal encapsulation film, and the tab assembly extends from the capping region to form a tab end. Along the length direction of the tab adhesive, the hot melt region includes a first overflow area, a hot melt main area, and a second overflow area. The hot melt main area corresponds to the capping region. The first overflow area extends from the hot melt main area toward the tab end, and the second overflow area extends from the hot melt main area toward the tab end. The length of the first overflow area is greater than the length of the second overflow area.
[0013] In one possible implementation, the length of the first overflow area is L3, and the length of the second overflow area is L4, wherein L3 and L4 satisfy the following relationship:
[0014] L3-L4≥10μm.
[0015] In one possible implementation, the tab adhesive includes an outer probe extending from the hot melt zone toward the direction away from the metal encapsulation film and an inner probe extending from the hot melt zone toward the inside of the metal encapsulation film.
[0016] In one possible implementation, the electrode tab includes an electrode tab body portion and an electrode tab pressing edge portion. In the width direction, the electrode tab pressing edge portion is located at both ends of the electrode tab body portion, and the electrode tab body portion and the electrode tab pressing edge portion are located within the coverage area formed by the body portion and the pressing edge portion.
[0017] In one possible implementation, the thickness of the reduced-thickness section is W1, the thickness of the non-reduced-thickness section is W2, the length of the second hot-melt zone is L2, and the length of the first hot-melt zone is L1. L1, L2, W1, and W2 satisfy the following relationship:
[0018] 1% < L1 W1 / L2 W2 < 60%.
[0019] In one possible implementation, the width of the edge segment is S1, the width of the thickened segment is S2, the thickness of the thickened segment is W1, and the thickness of the non-thickened segment is W2. W1, W2, S1, and S2 satisfy the following relationship:
[0020] 0 < W1 ≤ 0.9 W2, 20%≤S2 / S1≤80%.
[0021] In one possible implementation, along the thickness direction of the tab adhesive, the thickness of the tab body is W3, the thickness of the end of the tab pressing portion away from the tab body is W4, and the pressing width of the pressing segment is S3. W3, W4, and S3 satisfy the following relationship:
[0022] 0.3≤W4 / W3≤0.7, 0.7≤S3 / W3≤2.3.
[0023] In one possible implementation, the end of the edge segment forms an edge end, and the thickness of the edge segment gradually decreases towards the edge end.
[0024] In one possible implementation, the tab adhesive includes a laminated conductive layer, an intermediate layer, and a heat-sealing layer. Along the lamination direction, the thickness of the tab adhesive is H1, and the thickness of the conductive layer is H2. H1 and H2 satisfy the following relationship:
[0025] H1=50μm~600μm, H2 / H1=0.35~0.5. Attached Figure Description
[0026] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.
[0027] Figure 1 A schematic diagram of the structure of a battery according to an embodiment of this application is shown;
[0028] Figure 2 A schematic diagram of another battery structure provided according to an embodiment of this application is shown;
[0029] Figure 3 A partially enlarged schematic diagram of a battery according to an embodiment of this application is shown;
[0030] Figure 4 It shows Figure 3 A cross-sectional view of the middle section passing through the second hot melt zone;
[0031] Figure 5 The diagram shows the interface changes between the main hot melt zone and the second overflow zone;
[0032] Figure 6 The diagram shows the interface changes between the hot melt main area and the first overflow area;
[0033] Figure 7 A schematic diagram of the structure of an electrode adhesive according to an embodiment of this application is shown;
[0034] Figure 8 This diagram shows a schematic representation of the structure of a battery before hot pressing, according to an embodiment of this application.
[0035] Figure 9 This diagram illustrates the structure of a battery after hot pressing, according to an embodiment of this application.
[0036] Figure 10 A schematic diagram of the edge segment of an electrode adhesive according to an embodiment of this application is shown;
[0037] Figure 11 A schematic diagram of the pressing section of an electrode tab adhesive according to an embodiment of this application is shown;
[0038] Figure 12 A schematic diagram of another tab adhesive provided according to an embodiment of this application is shown;
[0039] Figure 13 A schematic diagram of the structure of another type of tab adhesive provided according to an embodiment of this application is shown;
[0040] Figure 14 A schematic diagram of the structure of another type of tab adhesive provided according to an embodiment of this application is shown;
[0041] Figure 15 A schematic diagram of the structure of yet another type of tab adhesive provided according to an embodiment of this application is shown;
[0042] Figure 16 A schematic diagram of the structure of another type of tab adhesive provided according to an embodiment of this application is shown;
[0043] Figure 17 A schematic diagram of the structure of another tab adhesive provided according to an embodiment of this application is shown.
[0044] Figure label:
[0045] 100 - Metal encapsulation film; 110 - Top sealing area;
[0046] 200 - Cell assembly; 210 - Tab assembly; 211 - Tab adhesive; 212 - Tab; 211a - Outer detection area; 211b - Inner detection area; 2111 - Main body section; 2112 - Edge section; 2113 - Edge pressing section; 2121 - Tab main body; 2122 - Tab edge pressing section; 2112a - Thickened section; 2112b - Non-thickened section; 2112c - Stepped notch; 2112d - Arc-shaped notch;
[0047] 300 - Hot melt zone; 310 - First hot melt zone; 320 - Second hot melt zone; 300a - First overflow zone; 300b - Main hot melt zone; 300c - Second overflow zone;
[0048] 11 - First boundary line; 12 - Second boundary line; 13 - Third boundary line; 14 - Fourth boundary line.
[0049] The accompanying drawings illustrate specific embodiments of this application, which will be described in more detail below. These drawings and descriptions are not intended to limit the scope of the concept in any way, but rather to illustrate the concept of this application to those skilled in the art through reference to particular embodiments. Detailed Implementation
[0050] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0051] To form an integrated battery structure, after the cell assembly is manufactured, it can be encapsulated with an aluminum-plastic film, exposing the tabs of the cell assembly, thus forming a typical structure of a pouch lithium-ion battery.
[0052] Compared to rigid steel-cased batteries, pouch lithium-ion batteries offer advantages such as lighter weight and higher energy density, making them suitable for portable electronic devices, medical devices, and other applications requiring lightweight, high-capacity batteries. For pouch lithium-ion batteries, the sealing performance between the aluminum-plastic film and the cell assembly significantly impacts the overall performance. Insufficient sealing can lead to leakage and potentially cause safety incidents.
[0053] A battery cell assembly may include a positive electrode sheet, a negative electrode sheet, and a separator disposed between the positive and negative electrode sheets. Furthermore, a positive electrode tab is disposed on the positive electrode sheet, and a negative electrode tab is disposed on the negative electrode sheet. To form a seal between the aluminum-plastic film and the tabs, a positive electrode tab adhesive is wrapped around the outside of the positive electrode tab, and a negative electrode tab adhesive is wrapped around the outside of the negative electrode tab. The positive electrode tab adhesive has a similar shape to the positive electrode tab, and the negative electrode tab adhesive has a similar shape to the negative electrode tab. For ease of description, in the embodiments of this application, the positive electrode tab together with the positive electrode tab adhesive and the negative electrode tab together with the negative electrode tab adhesive are collectively referred to as a tab assembly; the positive electrode tab and the negative electrode tab are collectively referred to as a tab; and the positive electrode tab adhesive and the negative electrode tab adhesive are collectively referred to as tab adhesive. Therefore, a battery cell assembly may include a positive electrode sheet, a separator, a negative electrode sheet, and a tab assembly.
[0054] When encapsulating the aforementioned battery cell assembly, the aluminum-plastic film needs to be fused together with the tab adhesive. Generally speaking, both the tab and the tab adhesive have a certain thickness, which makes it easy for wrinkles to form at the end of the tab adhesive during the hot pressing process, thereby affecting the sealing performance between the aluminum-plastic film and the battery cell assembly.
[0055] Based on the above situation and problems, this application provides a battery, which is a soft-pack lithium-ion battery. The battery mainly includes a metal encapsulation film and a cell assembly disposed in the metal encapsulation film. The battery can eliminate or reduce wrinkles, thereby improving the sealing performance of the battery.
[0056] Specifically, to achieve the above objectives, the embodiments of this application have designed the tabs and tab adhesives with a reduced thickness section at their ends, so that the ends of the tab adhesives can form a good fusion bond with the aluminum-plastic film during the battery encapsulation process, thereby achieving the purpose of eliminating or reducing wrinkles.
[0057] In the embodiments of this application, the above-mentioned battery cell assembly can be a stacked structure or a wound structure.
[0058] In the embodiments of this application, the metal encapsulation film can be an aluminum-plastic film or a steel-plastic film.
[0059] In the embodiments of this application, the electrode tab can be an aluminum electrode tab, a nickel electrode tab, or a copper-plated nickel electrode tab.
[0060] Figure 1 A schematic diagram of the structure of a battery according to an embodiment of this application is shown; Figure 2 A schematic diagram of another battery structure provided according to an embodiment of this application is shown; Figure 3 A partially enlarged schematic diagram of a battery according to an embodiment of this application is shown; Figure 4 It shows Figure 3 A cross-sectional view of the middle section passing through the second hot melt zone; Figure 5The diagram shows the interface changes between the main hot melt zone and the second overflow zone; Figure 6 The diagram shows the interface changes between the hot melt main area and the first overflow area; Figure 7 A schematic diagram of the structure of an electrode adhesive 211 provided according to an embodiment of this application is shown.
[0061] In the embodiments of this application, please refer to Figures 1 to 7 The battery includes a metal encapsulation film 100 and a cell assembly 200, which is housed in the metal encapsulation film 100.
[0062] Understandably, during the battery manufacturing process, the metal encapsulation film 100 can be wrapped around the outer periphery of the cell assembly 200.
[0063] The battery cell assembly 200 includes a tab assembly 210 extending from one side of the metal encapsulation film 100. The tab assembly 210 includes a tab 212 and a tab adhesive 211 wrapped around the tab 212. Along the width direction of the tab adhesive 211, the tab adhesive 211 includes a main body segment 2111, an edge segment 2112 disposed at at least one end of the main body segment 2111 in the width direction, and a pressing edge segment 2113 connecting the main body segment 2111 and the edge segment 2112. The thickness of the pressing edge segment 2113 at the end near the main body segment 2111 is greater than the thickness of the pressing edge segment 2113 at the end away from the main body segment 2111. Specifically, the thickness of the pressing edge segment 2113 can gradually decrease from the end near the main body segment 2111 to the end away from the main body segment 2111.
[0064] The tabs are typically made of metal, such as the aluminum tabs and nickel tabs mentioned earlier. The function of the tab adhesive 211 is to form a fusion bond with the metal encapsulation film 100. It should be understood that the tab adhesive 211 has a structure corresponding to the tab 212. Each component of the tab adhesive 211 corresponds to a corresponding structural part of the tab 212. For example, the main body segment 2111 of the tab adhesive 211 corresponds to the tab body portion 2121 of the tab, which can act as either the positive or negative terminal. The pressing edge segment 2113 corresponds to the tab pressing edge portion 2122 of the tab 212.
[0065] It should be understood that the aforementioned main body segment 2111, edge segment 2112, and pressing edge segment 2113 represent the shape of the tab adhesive 211 before hot melting, and are designed to match the shape of the tab 212. After hot melting is completed, as can be seen from the following embodiments, the tab adhesive 211 can form a hot melting zone 300, an outer probe zone 211a, and an inner probe zone 211b.
[0066] The edge segment 2112 includes a reduced-thickness segment 2112a and a non-reduced-thickness segment 2112b. Along the thickness direction of the tab adhesive 211, the thickness of the reduced-thickness segment 2112a is smaller than that of the non-reduced-thickness segment 2112b. It can be understood that by setting the edge segment 2112 to include the reduced-thickness segment 2112a, the thickness of the end of the edge segment 2112 can be reduced, which is beneficial to forming a heat-fused connection with the metal encapsulation film 100. During the process of forming a connection between the metal encapsulation film 100 and the reduced-thickness segment 2112a, the two will not form a large degree of bending, thereby reducing or eliminating wrinkles.
[0067] The tab adhesive 211 is thermally bonded to the metal encapsulation film 100 to form a thermal fusion region 300. Along the length direction of the tab adhesive 211, the thermal fusion region 300 includes a first thermal fusion region 310 corresponding to the thickened section 2112a and a second thermal fusion region 320 corresponding to the non-thickened section 2112b. The length of the first thermal fusion region 310 is less than the length of the second thermal fusion region 320.
[0068] During the hot pressing process, the length of the hot melt zone 300 can be controlled by setting process parameters. The ultimate goal is to make the first hot melt zone 310 correspond to the reduced thickness section 2112a and the second hot melt zone 320 correspond to the non-reduced thickness section 2112b.
[0069] Regarding the hot-melt zone 300, it's understandable that, overall, a longer hot-melt zone 300 is more beneficial for improving the battery's sealing performance. Specifically, the secondary heating during hot melting causes the tab adhesive 211 to recrystallize, significantly increasing the proportion of the crystalline area and enhancing crystallinity. This reduces and narrows the channels for moisture penetration, thus improving sealing performance. Conversely, when the hot-melt zone 300 is short, the solvent swelling of the tab adhesive 211 during battery charging and discharging can easily create electron channels, leading to problems such as corrosion spots, incomplete sealing, decreased edge resistance, and increased edge voltage at the battery's top, greatly reducing battery life. Furthermore, because the non-thickness-reduced section 2112b is closer to the edge of the tab, a shorter second hot-melt zone 320 can result in insufficient filling of the encapsulation triangle area, increasing the risk of battery leakage.
[0070] Therefore, it is understood that in this embodiment of the application, the thickening section 2112a is configured to include the thickening section 2112a and the non-thickening section 2112b, and the length of the second hot melt zone 320 is made greater than the length of the first hot melt zone 310 by means of process. This can achieve the purpose of effectively balancing the service life of the battery while ensuring the overall packaging performance of the battery, and can prevent leakage.
[0071] In this embodiment, due to the provision of the reduced thickness section 2112a in the edge section 2112, and the thickness of the end of the pressing section 2113 near the main body section 2111 being greater than the thickness of the end of the pressing section 2113 away from the main body section 2111, it is beneficial for the tab adhesive 211 to form a heat-fused connection with the metal encapsulation film 100. During the connection process between the metal encapsulation film 100 and the tab adhesive 211, a transition along the thickness direction can be formed between the metal encapsulation film 100 and the tab adhesive 211, which can avoid poor encapsulation caused by excessive thickness of the metal encapsulation film 100. The metal encapsulation film 100 and the tab adhesive 211 will not form a large degree of bending, thereby reducing or eliminating wrinkles and improving the sealing performance of the battery. On the other hand, the hot melt zone 300 in this embodiment includes a first hot melt zone 310 corresponding to the thickening section 2112a and a second hot melt zone 320 corresponding to the non-thickening section 2112b. By setting the length of the second hot melt zone 320 to be greater than the length of the first hot melt zone 310, the battery life can be effectively balanced while ensuring the overall battery packaging performance, and leakage can be prevented.
[0072] In some embodiments, please refer to Figure 3 and Figure 4 The length of the second hot melt zone 320 is L2, and the length of the first hot melt zone 310 is L1. L1 and L2 satisfy: L2-L1≥5μm.
[0073] By controlling the gap between the second hot melt zone 320 and the first hot melt zone 310 within the aforementioned size range, the overall sealing performance of the battery can be guaranteed and the battery life can be improved.
[0074] In some embodiments, please refer to Figure 3 and Figure 4 The battery has a capping region 110 formed on one side edge of the metal encapsulation film 100. The tab assembly 210 extends from the capping region 110 and forms a tab end. Along the length direction of the tab adhesive 211, the hot melt region 300 includes a first overflow region 300a, a hot melt main region 300b, and a second overflow region 300c. The hot melt main region 300b corresponds to the capping region 110. The first overflow region 300a extends from the hot melt main region 300b toward the tab end. The second overflow region 300c extends from the hot melt main region 300b toward the tab end. The length of the first overflow region 300a is greater than the length of the second overflow region 300c.
[0075] Understandably, during hot pressing, the hot pressing head needs to act on the metal encapsulation film 100. The area acted upon by the hot pressing head is the aforementioned sealing area 110. The hot pressing head can seal the edge of the battery. Understandably, during the hot pressing process, the metal encapsulation film 100 and the tab adhesive 211 will flow towards both sides of the hot pressing head under hot pressing, thereby forming the main hot melt area 300b, the first adhesive overflow area 300a, and the second adhesive overflow area 300c.
[0076] It should be noted that the shape and size of the hot-melt zone 300 can be changed by altering the structure and dimensions of the hot-pressed head and controlling the relevant process parameters.
[0077] Can be combined Figure 5 and Figure 6 To understand the hot melt zone main area 300b, the first overflow area 300a, and the second overflow area 300c, please refer to the following: Figure 5 The second overflow area 300c is located at one end of the main area 300b of the hot melt zone, away from the tab end. The length of the second overflow area 300c is defined as the shortest distance from the edge of the top sealing area 110 to the position where the tab adhesive 211 separates from the metal encapsulation film 100, i.e. Figure 5 The distance between the first boundary line 11 and the second boundary line 12, where the first boundary line 11 is the starting point where adhesive overflow begins and expands outward, and the second boundary line 12 is the point where the tab adhesive 211 separates from the metal encapsulation film 100. Please refer to [further details]. Figure 6 The first overflow area 300a is located at one end of the main area 300b of the hot melt zone, near the tab end. The length of the first overflow area 300a is also defined as the shortest distance from the edge of the top sealing area 110 to the position where the tab adhesive 211 separates from the metal encapsulation film 100, i.e. Figure 6 The distance between the third boundary line 13 and the fourth boundary line 14, wherein the third boundary line 13 is the starting position where the adhesive begins to overflow and expand outward, and the fourth boundary line 14 is the position where the tab adhesive 211 separates from the metal encapsulation film 100.
[0078] Therefore, it is understandable that the overall length of the hot melt zone 300 can be characterized by the distance between the second boundary line 12 and the fourth boundary line 14.
[0079] The above embodiment controls the length of the first overflow region 300a to be greater than the length of the second overflow region 300c, resulting in a shorter overflow region length on the inner side of the cell compared to the outer side. This less overflow on the inner side reduces side reactions between the electrolyte and the tab adhesive 211, preventing damage to the tab adhesive 211 structure and effectively maintaining the battery's sealing performance. Furthermore, in the event of thermal runaway, the shorter internal overflow region can act as a weak pressure relief area, improving battery safety.
[0080] In some specific embodiments, the length of the first overflow region 300a is L3, and the length of the second overflow region 300c is L4. L3 and L4 satisfy the relationship: L3-L4≥10μm.
[0081] By controlling the length difference between the first overflow area 300a and the second overflow area 300c within the aforementioned size range, the strength matching between the outer edge and the inner edge of the battery can be reasonably configured, thereby improving the overall sealing performance of the battery.
[0082] In some embodiments, the tab 212 includes a tab body portion 2121 and a tab pressing edge portion 2122. In the width direction, the tab pressing edge portion 2122 is located at both ends of the tab body portion 2121. The tab body portion 2121 and the tab pressing edge portion 2122 are located within the coverage area formed by the body segment 2111 and the pressing edge segment 2113. The thickness of the tab pressing edge portion 2122 at the end near the tab body portion 2121 is greater than the thickness of the tab pressing edge portion 2122 at the end away from the tab body portion 2121.
[0083] The above-described structural design of the tab 212 is beneficial for the arrangement of the tab 212 along the width direction, which can increase the width dimension of the tab 212 and thus increase the electron transmission path. In addition, by setting the tab body 2121 and the tab pressing edge 2122 to be located within the coverage area formed by the body section 2111 and the pressing edge section 2113, the tab body 2111 and the tab pressing edge 2113 can be effectively wrapped, which is beneficial for forming a seal between the tab 211 and the metal encapsulation film 100.
[0084] Figure 8 This diagram shows a schematic representation of the structure of a battery before hot pressing, according to an embodiment of this application. Figure 9 A schematic diagram of the structure of a battery after hot pressing is shown according to an embodiment of this application.
[0085] In some embodiments, please refer to the reference Figure 3 , Figure 8 and Figure 9 The tab adhesive 211 includes an outer probe region 211a extending from the heat-melting zone 300 in a direction away from the metal encapsulation film 100 and an inner probe region 211b extending from the heat-melting zone 300 to the inside of the metal encapsulation film 100.
[0086] After hot pressing is completed, the outer probe area 211a and the inner probe area 211b are the parts of the tab adhesive 211 that did not participate in the hot melting. In other words, for the tab adhesive 211, a part of it participated in the hot melting connection, and its two ends formed the outer probe area 211a and the inner probe area 211b respectively.
[0087] Figure 10A schematic diagram of the structure of the edge segment 2112 of an electrode adhesive 211 provided according to an embodiment of this application is shown.
[0088] In some embodiments, please refer to Figure 3 and Figure 10 The thickness of the reduced-thickness section 2112a is W1, the thickness of the non-reduced-thickness section 2112b is W2, the length of the second hot-melt zone 320 is L2, and the length of the first hot-melt zone 310 is L1. L1, L2, W1, and W2 satisfy the relationship: 1% < L1 W1 / L2 W2 < 60%.
[0089] It is understandable that the above relationship can relate the dimensional relationships between the reduced thickness section 2112a, the non-reduced thickness section 2112b, the first hot melt zone 310, and the second hot melt zone 320. This is achieved by associating the thickness of the reduced thickness section 2112a and the corresponding length of the first hot melt zone 310 with the thickness of the non-reduced thickness section 2112b and the corresponding length of the second hot melt zone 320, and by linking L1... W1 / L2 When W2 is controlled within the above range, it can provide a reference benchmark for the production and manufacturing of the thickened section 2112a and the hot melt zone 300, and can ensure the sealing performance of the battery.
[0090] When L1 W1 / L2 When W2 is too small, the thickness difference between the reduced-thickness section 2112a and the non-reduced-thickness section 2112b is significant, which can easily affect the stability of the tab adhesive 211 and increase the manufacturing difficulty of the tab adhesive 211. When L1 W1 / L2 When W2 is too large, it not only increases the probability of wrinkles forming at the tabs of the packaged battery, but also reduces the resistance to moisture corrosion at the top, thus affecting the battery's lifespan. Therefore, L1... W1 / L2 W2 should be controlled at 1% < L1 W1 / L2 Within the range of W2 < 60%, after heat sealing of the tab adhesive 211 and the metal encapsulation film 100, the retention rate of the tab adhesive 211 can reach 30%-70%, which meets the process requirements and ensures that the top of the battery cell assembly 200 achieves a good sealing effect under high temperature and high humidity conditions.
[0091] In some embodiments, please refer to Figure 10 The width of edge segment 2112 is S1, the width of thickened segment 2112a is S2, the thickness of thickened segment 2112a is W1, and the thickness of non-thickened segment 2112b is W2. W1, W2, S1, and S2 satisfy the relationship: 0 < W1 ≤ 0.9 W2, 20%≤S2 / S1≤80%.
[0092] When W1 is too small, it indicates that the thickness of the reduced section 2112a is too thin, which can easily affect the stability of the tab adhesive 211 and increase the manufacturing difficulty of the tab adhesive 211. When W1 is too large, it indicates that the thickness of the reduced section 2112a is too thick, which is not effective enough in suppressing wrinkles, thus making it difficult to form a good sealing effect. The above size settings can control the overall size of the edge section 2112 and the proportion of the reduced section 2112a in the edge section 2112, and can reasonably configure the various dimensions of the reduced section 2112a in the edge section 2112, thereby improving the heat-fusion effect between the tab adhesive 211 and the metal encapsulation film 100.
[0093] Figure 11 A schematic diagram of the pressing section 2113 of an electrode tab adhesive 211 provided according to an embodiment of this application is shown.
[0094] In some embodiments, please refer to Figure 7 and Figure 11 Along the thickness direction of the tab adhesive 211, the thickness dimension of the main body section 2111 is W3, the thickness dimension of the pressing section 2113 is W4, and the width of the pressing section 2113 is S3. W3, W4 and S3 satisfy the following relationship: 0.3≤W4 / W3≤0.7, 0.7≤S3 / W3≤2.3.
[0095] The thickness of the pressing section 2113 is approximately 30% to 70% of that of the main body section 2111. This thickness is designed to complement the shape of the tabs, preventing damage to the cell assembly 200 and avoiding leakage. Specifically, when the thickness of the pressing section 2113 is less than 30% of the thickness of the main body section 2111, the edge of the tab corresponding to the main body section 2111 is too sharp and may scratch or puncture the foil and metal encapsulation film 100, causing a short circuit in the cell. When the thickness of the pressing section 2113 is greater than 70% of the thickness of the main body section 2111, voids may form at the junction of the tab edge and the tab adhesive 211, posing a risk of leakage to the cell assembly 200.
[0096] The width of the pressing section 2113 is approximately 0.7-2.3 times the thickness of the main body section 2111, which can effectively enhance the sealing performance of the battery.
[0097] It is understandable that, for the same tab, the widths of the two pressing segments 2113 at its two ends can be the same or different.
[0098] Figure 12 A schematic diagram of another tab adhesive 211 provided according to an embodiment of this application is shown; Figure 13 A schematic diagram of the structure of another type of tab adhesive 211 provided according to an embodiment of this application is shown; Figure 14 A schematic diagram of the structure of another tab adhesive 211 provided according to an embodiment of this application is shown; Figure 15 A schematic diagram of the structure of another type of tab adhesive 211 provided according to an embodiment of this application is shown; Figure 16 A schematic diagram of the structure of another tab adhesive 211 provided according to an embodiment of this application is shown; Figure 17 A schematic diagram of the structure of another tab adhesive 211 provided according to an embodiment of this application is shown.
[0099] In conjunction with the foregoing, one of the main design concepts of this application embodiment is to form a reduced-thickness section 2112a in the edge segment 2112. For this purpose, the tab adhesive 211 can have various structural forms. For example, the edge segment 2112 of the tab adhesive 211 can have a multi-layered structure, a trapezoidal shape, or an arc shape, etc., with the end region of the edge segment 2112 forming the reduced-thickness section 2112a. Alternatively, the end of the edge segment 2112 can be formed as an edge end, and the thickness of the edge segment 2112 gradually decreases towards the end. Furthermore, the structures of the two edge segments 2112 on the tab adhesive 211 can be the same or different.
[0100] For example, please refer to Figure 12 The edge segment 2112 has a three-segment structure, wherein the structure at the end forms a reduced-thickness segment 2112a, and the two edges can have the same structure.
[0101] For example, please refer to Figure 13 The thickened section 2112a is a trapezoidal section with gradually decreasing dimensions, and the two edge sections 2112 have the same structure.
[0102] For example, please refer to Figure 14 The thickened section 2112a is a tapered section with gradually decreasing size, and the two edge sections 2112 have the same structure.
[0103] For example, please refer to Figure 15 One edge segment 2112 has a structure with one side flush and the other side having a stepped notch 2112c, wherein the stepped notch 2112c is located at the position of the thickened segment 2112a. The other edge segment 2112 has a structure with one side flush and the other side having an arc-shaped notch 2112d, wherein the arc-shaped notch 2112d is located at the position of the thickened segment 2112a.
[0104] For example, please refer to Figure 16 Both variable edge segments 2112 have a structure with one side flush and the other side having a stepped notch 2112c, where the notch is located in the thickened segment 2112a.
[0105] For example, please refer to Figure 17Both variable edge segments 2112 have a structure with one side flush and the other side having an arc-shaped notch 2112d, where the arc-shaped notch 2112d is located in the thickened segment 2112a.
[0106] The above description is merely an example illustrating the specific structure of the tab adhesive 211. It is understood that in other embodiments, the tab adhesive 211 may be constructed into other structures.
[0107] In some embodiments, the tab adhesive 211 includes a conductive layer, an intermediate layer and a heat-sealing layer stacked together. Along the stacking direction, the thickness of the tab adhesive 211 is H1, and the thickness of the conductive layer is H2. H1 and H2 satisfy the following relationship: H1 = 50 μm ~ 600 μm, H2 / H1 = 0.35 ~ 0.5.
[0108] In the above embodiments, the conductive layer can be made of an insulating material that is easy to connect with the tab, and the thickness of the conductive layer accounts for 35%-50% of the total thickness of the tab adhesive 211, and the tab exhibits a good sealing effect.
[0109] To better understand the dimensional relationship and advantages between the reduced-thickness section 2112a and the non-reduced-thickness section 2112b of the tab adhesive 211 in the embodiments of this application, the following will be explained in conjunction with several embodiments and comparative examples.
[0110] Example 1
[0111] The batteries were heat-sealed under the following conditions: temperature 180℃, heat-sealing time 3 seconds, and heat-sealing pressure 0.3 MPa. The dimensions of the tab adhesive 211 were: W2 400 μm, W1 20 μm, S1 4 mm, and S2 2 mm. The proportions of wrinkles and leakage were observed in different groups of batteries. The leakage test involved placing the heat-sealed batteries in an environment of 60℃ and 95% humidity for 30 days and checking for leakage at the tabs. Each group consisted of 100 batteries.
[0112] Observations revealed that both the percentage of wrinkles and the percentage of leaks were 0.
[0113] The parameters and test results of Examples 2 to 15, and Comparative Examples 1 to 6 are detailed in the table below.
[0114] Example W2 / (μm) W1 / (μm) S1 / (mm) S2 / (mm) W1 / W2 S2 / S1 L2 / (μm) L1 / (μm) Pleat ratio Leakage ratio Example 1 400 20 4 2 5.0% 50% 4423 3954 0% 0% Example 2 400 50 4 2 12.5% 50% 4389 4023 0% 0% Example 3 400 100 4 2 25.0% 50% 4396 4124 0% 0% Example 4 400 150 4 2 37.5% 50% 4412 4197 2% 0% Example 5 400 200 4 2 50.0% 50% 4409 4287 3% 0% Example 6 400 300 4 2 75.0% 50% 4598 4301 7% 0% Example 7 400 50 4 0.5 12.5% 13% 4425 3891 5% 0% Example 8 400 50 4 1 12.5% 25% 4427 3995 1% 0% Example 9 400 50 4 1.2 12.5% 30% 4412 4203 0% 0% Example 10 400 50 4 1.8 12.5% 45% 4397 4008 0% 0% Example 11 400 50 4 2.2 12.5% 55% 4572 4261 0% 0% Example 12 400 50 4 2.5 100.0% 63% 4332 4187 0% 1% Example 13 400 50 4 3 95.0% 75% 4641 4500 0% 6% Example 14 400 50 4 3.5 5.0% 88% 4882 4674 0% 10% Comparative Example 1 400 400 / / 12.5% / / / 98% 0% Comparative Example 2 400 380 4 2 25.0% 50% 4438 4421 90% 0%
[0115] As can be seen from the above embodiments and comparative examples:
[0116] 1) The smaller the value of W2 / W1, the lower the probability of the battery wrinkling. W2 / W1 can preferably be ≤25%;
[0117] 2) When the S2 / S1 ratio is too low, the proportion of the thickening section is too small, and the effect of improving wrinkles is not significant. When it is too high, the proportion of the thickening section is too large, which can easily cause battery leakage. The preferred range of S2 / S1 is 30%~55%.
[0118] In the description of this application, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "upper", "lower", "front", "rear", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", "outer", etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings, and are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of this application.
[0119] In the description of this application, it should be understood that the terms "comprising" and "having" and any variations thereof used in the embodiments of this application are intended to cover non-exclusive inclusion. For example, a process, method, system, product, or device that includes a series of steps or units is not necessarily limited to those steps or units that are explicitly listed, but may include other steps or units that are not explicitly listed or that are inherent to such process, method, product, or device.
[0120] Unless otherwise expressly specified and limited, the terms "installation," "connection," "linking," "fixing," etc., should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the connection within two components or the interaction between two components. Those skilled in the art can understand the specific meaning of the above terms in this application according to the specific circumstances. Furthermore, the terms "first," "second," etc., are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated.
[0121] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
Claims
1. A battery, characterized in that, include: Metal encapsulation film; A battery cell assembly is housed within a metal encapsulation film. The battery cell assembly includes a tab assembly extending from one side of the metal encapsulation film. The tab assembly includes a tab and tab adhesive covering the tab. Along the width direction of the tab adhesive, the tab adhesive includes a main body segment, an edge segment disposed at at least one end of the main body segment along its width direction, and a pressing segment connecting the main body segment and the edge segment. The thickness of the pressing segment at the end closer to the main body segment is greater than the thickness of the pressing segment at the end farther from the main body segment. The edge segment includes a reduced-thickness segment and a non-reduced-thickness segment. Along the thickness direction of the tab adhesive, the thickness of the reduced-thickness segment is smaller than the thickness of the non-reduced-thickness segment. The tab adhesive and the metal encapsulation film are thermally fused together to form a thermally fused zone. Along the length of the tab adhesive, the thermally fused zone includes a first thermally fused zone corresponding to the thickened section and a second thermally fused zone corresponding to the non-thickened section. The length of the first thermally fused zone is less than the length of the second thermally fused zone.
2. The battery according to claim 1, characterized in that, The length of the second hot-melt zone is L2, and the length of the first hot-melt zone is L1. L1 and L2 satisfy the following relationship: L2-L1≥5μm.
3. The battery according to claim 2, characterized in that, The battery has a capping area formed on one side edge of the metal encapsulation film. The tab assembly extends from the capping area and forms a tab end. Along the length direction of the tab adhesive, the hot melt area includes a first overflow area, a hot melt main area, and a second overflow area. The hot melt main area corresponds to the capping area. The first overflow area extends from the hot melt main area toward the tab end, and the second overflow area extends from the hot melt main area toward the tab end. The length of the first overflow area is greater than the length of the second overflow area.
4. The battery according to claim 3, characterized in that, The length of the first overflow area is L3, and the length of the second overflow area is L4. L3 and L4 satisfy the following relationship: L3-L4≥10μm.
5. The battery according to claim 1, characterized in that, The electrode tab includes an electrode tab body and an electrode tab pressing edge. In the width direction, the electrode tab pressing edge is located at both ends of the electrode tab body, and the electrode tab body and the electrode tab pressing edge are located within the coverage area formed by the body segment and the pressing edge segment.
6. The battery according to any one of claims 1 to 5, characterized in that, The thickness of the reduced-thickness section is W1, the thickness of the non-reduced-thickness section is W2, the length of the second hot-melt zone is L2, and the length of the first hot-melt zone is L1. L1, L2, W1, and W2 satisfy the following relationship: 1% <L1 W1 / L2 W2<60%.
7. The battery according to any one of claims 1 to 5, characterized in that, The width of the edge segment is S1, the width of the thickened segment is S2, the thickness of the thickened segment is W1, and the thickness of the non-thickened segment is W2. W1, W2, S1, and S2 satisfy the following relationship: 0<W1≤0.9 W2, 20%≤S2 / S1≤80%.
8. The battery according to claim 5, characterized in that, Along the thickness direction of the tab adhesive, the thickness of the tab body is W3, the thickness of the end of the tab pressing section away from the tab body is W4, and the pressing width of the pressing section is S3. W3, W4, and S3 satisfy the following relationship: 0.3≤W4 / W3≤0.7, 0.7≤S3 / W3≤2.
3.
9. The battery according to any one of claims 1 to 5, characterized in that, The end of the edge segment forms an edge end, and the thickness of the edge segment gradually decreases towards the edge end.
10. The battery according to any one of claims 1 to 5, characterized in that, The tab adhesive comprises a conductive layer, an intermediate layer, and a heat-sealing layer stacked together. Along the stacking direction, the thickness of the tab adhesive is H1, and the thickness of the conductive layer is H2. H1 and H2 satisfy the following relationship: H1=50μm~600μm, H2 / H1=0.35~0.5.